Implementasi Green Economy melalui Pengembangan Usaha Magost (Mogot Block Soldier FLY) - Asriah Syam; St Salmah Sharon; Mustika Kusuma Basir; Harmina Harmina; Monalisa Monalisa (PELITA NUSA TENGGARA, 2026)
The increasing volume of organic waste and its limited utilization as an economic resource remain major environmental and social challenges at the local level. The green economy concept offers a development approach that emphasizes resource efficiency, environmental sustainability, and community welfare improvement. This Community Service Program aims to implement green economy principles through the development of the Magost business (Maggot Block Black Soldier Fly) as an alternative model for value-added organic waste management. The method applied was an educational approach through workshops, including material delivery, interactive discussions, and hands-on practice in Black Soldier Fly cultivation and maggot processing into Magost. The activity was conducted on Tuesday, January 13, 2026, at the Universitas Muhammadiyah Bone campus, involving students and the target community. The results indicate an improvement in participants’ knowledge and skills related to organic waste management, BSF cultivation, and Magost production as an environmentally friendly product. Active community participation during the workshops reflects strong interest and the potential sustainability of the program. The implications of this activity include the creation of green economy–based business opportunities, increased environmental awareness, and the establishment of an initial Magost business model that can be further developed. Overall, this community service program demonstrates that an educational workshop-based approach is effective in encouraging the implementation of a community-based green economy.